2016
DOI: 10.1093/toxsci/kfw114
|View full text |Cite
|
Sign up to set email alerts
|

Methoxychlor and Vinclozolin Induce Rapid Changes in Intercellular and Intracellular Signaling in Liver Progenitor Cells

Abstract: Methoxychlor (MXC) and vinclozolin (VIN) are well-recognized endocrine disrupting chemicals known to alter epigenetic regulations and transgenerational inheritance; however, non-endocrine disruption endpoints are also important. Thus, we determined the effects of MXC and VIN on the dysregulation of gap junctional intercellular communication (GJIC) and activation of mitogen-activated protein kinases (MAPKs) in WB-F344 rat liver epithelial cells. Both chemicals induced a rapid dysregulation of GJIC at non-cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Importantly, we demonstrated applicability of our innovative multiparametric SL-DT assay for variety of in vitro cell types such as liver cells (WB-F344), lung cells (BEAS-2B, HBE1) or testicular cells (TM4 and TM3 cells), which all are GJIC-competent cells commonly used for the assessment of GJIC in response to different chemicals [50][51][52][53][54] or physical treatments 55 . All these cell types express connexin 43 51,56,57 , which is widely expressed in many cell types (especially in the epithelial cells) and whose gap junction channels are diffusible for Lucifer Yellow fluorescent dye 58 .…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, we demonstrated applicability of our innovative multiparametric SL-DT assay for variety of in vitro cell types such as liver cells (WB-F344), lung cells (BEAS-2B, HBE1) or testicular cells (TM4 and TM3 cells), which all are GJIC-competent cells commonly used for the assessment of GJIC in response to different chemicals [50][51][52][53][54] or physical treatments 55 . All these cell types express connexin 43 51,56,57 , which is widely expressed in many cell types (especially in the epithelial cells) and whose gap junction channels are diffusible for Lucifer Yellow fluorescent dye 58 .…”
Section: Discussionmentioning
confidence: 94%
“…Since MAPKs and their pathways are crucial for healthy liver function [ 49 ] and implicated in the control of GJIC [ 45 ], the changes in the activity of MAPK-Erk1/2 were investigated in response to phthalates in rat liver oval WB-F344 cells. After 0.5 h exposure of WB-F344 cells to 10 nM TPA (12-O-tetradecanoylphorbol 13-acetate), which was used as a positive control and known GJIC inhibitor and tumor promoter, rapidly and significantly increased (~30-fold increase) the levels of phosphorylated, i.e., activated, MAPK-Erk1 and 2 ( Figure 4 ; original, uncropped and unadjusted images in Figures S6–S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Connexin 43 is the most abundant and studied connexin type, whose activity and function can be regulated by the direct phosphorylation caused by many kinases, including MAPK-Erk-1/2 [ 39 , 41 , 75 ]. While the activation of MAPK kinases is considered to be one of the mechanisms of GJIC dysregulation [ 41 , 76 , 77 ], it has been reported that various environmental toxicants and endocrine disrupters can dysregulate GJIC via mechanisms independent from the MAPK-Erk1/2 pathway, even when MAPK-Erk1/2 activation is associated with GJIC dysregulation [ 41 , 43 , 44 , 45 ]. Although GJIC-inhibiting phthalates also activated the MAPK-Erk1/2 pathways in our study, the rapid MAPK-Erk1/2 activation caused by phthalates from Groups E and F was not necessarily associated with the rapid inhibition of GJIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, animals contract MXC toxicity result several toxicological implications as ovarian toxicity, 77 where it causes impairment of ovarian follicular development and other ovarian function 77,86 leading to reproductive tract malformations in the male offspring. 87 MXC hepto-toxicity results in significant reduction in total serum protein rather than marked elevation in hepatic marker enzymes(ALT, AST & ALP) 76 as well as changes in inter and intra cellular signaling. 88 Histopathologically, there is changes in hepatocytes 76,89 owing to induction changes in mRNA abundance of genes in the liver and testes, 90 where alterations involved in regulations of gene expression, tissue development, function and homeostasis, could also contribute to transgenerational epigenetic effects of endocrine disruptors.…”
Section: Amelioration Effect Of Eep Against Induced Methoxychlor (Mxcmentioning
confidence: 99%